Prevalenceof abdominal aortic aneurysm among stage 3-4 chronic kidney disease patients aged 55 years and older - Karaarslan Cengiz, O.; Nergizoglu, G. (Ukrainian Journal of Nephrology and Dialysis, 2020)
The risk of cardiovascular disease begins to increase from the early stages of chronic kidney disease (CKD). Abdominal aortic aneurysms are the most common arterial aneurysms of peripheral arterial diseases. The frequency of abdominal aortic aneurysm varies according to the population studied. This study aimed to determine the prevalence of abdominal aortic aneurysm in patients with stage 3-4 CKD and investigate CKD is a risk factor for abdominal aortic aneurysm formation. Methods. Patients aged 55 years and older who were followed up in the internal medicine outpatient clinics were enrolled. Two hundred CKD patients with glomerular filtration rates between 15-59 mL/min per 1.73 m2 were included in the study group, and 110 patients with glomerular filtration rates of 60 mL/min per 1.73 m2 or above were assigned to the control group. An ultrasonography device with a 3.5 MHz probe was used for screening. Abdominal aortic diameters of 3 cm and above were accepted as abdominal aortic aneurysms. Results. Eighteen patients in the study group (9%) and four in the control group (3.6%) had an abdominal aortic aneurysm. The prevalence of abdominal aortic aneurysms was higher in the CKD group. However, the difference was not statistically significant (p=0.078). Moreover, the median aortic diameter was 21.8 mm (14-44 mm) in the study group, compared to 21.0 mm (14-46 mm) in the control group. The prevalence of the abdominal aortic aneurysm was 14.9% in stage 4 CKD patients and 6% in stage 3 CKD patients (p=0.038). Conclusion. An abdominal aortic aneurysm is more common in patients with CKD although it does not reach statistical significance. The median aortic diameter was significantly wider in CKD patients compared to the control group . The prevalence of abdominal aortic aneurysm increased with an increase in the CKD stage .